Medication utilization in traumatic brain injury patients—insights from a population-based matched cohort study - Molero, Yasmina; Sharp, David J.; D’Onofrio, Brian M.; Lichtenstein, Paul; Larsson, Henrik; Fazel, Seena; Rostami, Elham (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI) is associated with health problems across multiple domains and TBI patients are reported to have high rates of medication use. However, prior evidence is thin due to methodological limitations. Our aim was thus to examine the use of a wide spectrum of medications prescribed to address pain and somatic conditions in a population-based cohort of TBI patients, and to compare this to a sex-and age-matched cohort. We also examined how patient factors such as sex, age, and TBI severity were associated with medication use. We assessed Swedish nationwide registers to include all individuals treated for TBI in hospitals or specialist outpatient care between 2006 and 2012. We examined dispensed prescriptions for eight different non-psychotropic medication classes for the 12 months before, and 12 months after, the TBI. We applied a fixed-effects model to compare TBI patients with the matched population cohort. We also stratified TBI patients by sex, age, TBI severity and carried out comparisons using a generalized linear model. We identified 239 425 individuals with an incident TBI and 239 425 matched individuals. TBI patients were more likely to use any medication (Odds ratio [OR]=2.03, 95% Confidence Interval [CI]=2.00-2.05), to present with polypharmacy (OR=1.96, 95% CI=1.90-2.02), and to use each of the eight medication classes before their TBI, as compared to the matched population cohort. Following the TBI, TBI patients were more likely to use any medication (OR=1.83, 95% CI=1.80-1.86), to present with polypharmacy (OR=1.74, 95% CI=1.67-1.80), and to use all medication classes, although differences were attenuated. However, differences increased for antibiotics/antivirals (OR=2.02, 95% CI=1.99-2.05) and NSAIDs/antirheumatics (OR=1.62, 95% CI=1.59-1.65) post-TBI. We also found that females and older patients were more likely to use medications after their TBI than males and younger patients, respectively. Patients with more severe TBIs demonstrated increased use of antibiotics/antivirals and NSAIDs/antirheumatics than those with less severe TBIs. Taken together, our results point to poor overall health in TBI patients, suggesting that medical follow-up should be routine, particularly in females with TBI, and include a review of medication use to address potential polypharmacy.